The cosmological constant and dark energy - Churampi, Manuel (2023)
This article presents a review about the cosmological constant, the Friedmann-Lemaitre-Roberson-Walker cosmological model and its relationship with Einstein's gravitational theory and with Friedmann's equations. The observational evidence is evaluated and the experimental results of the accelerated expansion of the Universe are analyzed. Finally, the physical nature of the cosmological constant is described as a possibility of dark energy.